Analysis of the implementation of TOS upgrade and the use of VMT on operational performance with the accuracy of container data as an intervening variable at Terminal B of PT Belawan New Container Terminal - Darmansyah Nasution; Wan Suryani; Muhammad Yamin Siregar (Journal of Applied Business Administration, 2026)
This study analyzes the impact of Terminal Operating System (TOS) Upgrade Implementation and Vehicle Mounted Terminal (VMT) Usage on Operational Performance, with Container Data Accuracy serving as an intervening variable at Terminal B of PT Belawan New Container Terminal (BNCT), Medan. The research is driven by the strategic necessity of digital transformation to enhance port efficiency. Using a quantitative approach, data were collected from 63 operational employees and analyzed with SmartPLS 4.1. The results demonstrate that both TOS Upgrade Implementation and VMT Usage have a positive and significant effect on Container Data Accuracy. Furthermore, Container Data Accuracy is found to influence Operational Performance significantly and serves as a vital mediator in the relationship between VMT Usage and overall operational outcomes. These findings suggest that integrating hardware and software systems minimizes manual errors and streamlines workflow. Managerial implications recommend that port authorities prioritize sustained investment in TOS-VMT integration and workforce digital literacy to maintain a competitive advantage. Ultimately, enhancing digital infrastructure is essential for optimizing data integrity and accelerating container throughput in modern port logistics.